2019
DOI: 10.1136/bmjopen-2018-028669
|View full text |Cite
|
Sign up to set email alerts
|

‘I’m here to save my life’: a qualitative study of experiences navigating a cryotherapy referral system for human papillomavirus-positive women in western Kenya

Abstract: BackgroundWe sought to understand the beliefs, social norms and logistical factors that affect human papillomavirus (HPV)-positive women’s uptake of cryotherapy treatment as part of a two-part cervical cancer screening strategy in rural Kenya.MethodsIn-depth interviews within a parent cluster-randomised trial.SettingGovernment-run county hospital in western Kenya.Participants273 of 372 (73.4%) HPV-positive women who underwent cryotherapyResultsMany women feared that an HPV infection meant they would develop ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…A study in Kenya ( Lunsford et al. , 2017 ) showed that women were willing to undergo the screening if they were given incentives or if they were reimbursed by the state for transportation ( Huchko et al. , 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…A study in Kenya ( Lunsford et al. , 2017 ) showed that women were willing to undergo the screening if they were given incentives or if they were reimbursed by the state for transportation ( Huchko et al. , 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a study conducted in Kenya, financial support was key facilitators of HPV-positive women’s treatment access [ 45 ]. Due to the high cost of colposcopy in Iran, referral of women to government-funded clinics (by HCPs) may improve women’s adherence to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although awareness of the importance of CC screening is increasing ( 9 ), only 16–19% of eligible Kenyan women 18–69 years old are screened for CC ( 10 ). These low rates of screening contribute to 50–80% of cases identified in advanced stages of CC ( 11 – 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Kenyan guidelines call for a “screen and treat” protocol for women with pre-cancerous lesions identified by VIA/VILI (when PAP or HPV testing is unavailable), in which treatment is administered on the same clinic visit as diagnosis to minimize patient burden, treatment delay, and loss to follow-up (LTFU) ( 14 ). However, in a survey of 12 hospitals across 7 counties, only 25% of facilities had a functional cryotherapy machine ( 9 ), allowing them to offer services compliant with these guidelines. Even amongst those who offer same day services, supply stock outs, C02 shortages for the cryotherapy machine, and lack of trained providers available to perform the procedure can delay treatment and cause increased burden on patients ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%